Firm size, book to market equity, and security returns : evidence from the Indonesian Shari'ah stocks - Ferdian, Ilham Reza (Kulliyyah of Economics and Management Science,International Islamic University Malaysia, 2009)
Capital market is one of indicators which may give measurement on economic growth of a country, including Indonesia. In the country, main reference for any investment decisions which related with Islamic capital market instruments is based on Shanah Securities List (SSL) issued by Bapepam-LK Investors who put funds in the Indonesian Shariah Stocks can make investment decisions by monitoring the performance of these stocks This can be done through using return measurement methods such as Capital Asset Pricing Model (CAPM) proposed by Sharpe (1964). However, Fama and French (1992) argue that size, EPR, debt-to-equity and book-to market ratio have explanatory power to stock returns. Further, Fama and French (1993) find that the most significant variables among those mentioned above in explaining the stock returns are size, book-to-market ratio, and market beta. This study finds that the market beta alone is not sufficient to describe the variation in average equity returns for Indonesian Shariah Stocks over the period of 14 September to 25 September 2009. Additionally, this study also finds that even though size and value premia exists in the Indonesian Shariah Stocks; the market factor is still most important factor among the Fama & French Three Factors Model.